Word Skipping in Reading English as a Foreign Language: Evidence from Eye Tracking - Dolgunsöz , Emrah; Sarıçoban , Arif (East European Journal of Psycholinguistics, 2016)
During reading, readers never fixate on all words in the text; shorter words sometimes gain zero fixation and skipped by the reader. Relying on E-Z Reader Model, this research hypothesized that a similar skipping effect also exists for a second language. The current study examined word skipping rates in EFL (English as a Foreign Language) with 75 EFL learners by using eye tracking methodology. The results showed that word skipping was affected by EFL reading proficiency significantly and articles (a, an, the) were skipped more than content words. Furthermore, more skilled learners were observed to have less fixation count and skipped more words during reading while less skilled learners employed more fixations and skipped less words. Eye tracking as a novel method to observe learner development and progress in EFL reading was also discussed. References Altarriba, J., Kroll, J. F., Sholl, A.. & Rayner, K. (1996). The influence of lexical and conceptual constraints on reading mixed-language sentences: Evidence from eye fixations and naming times. Memory & Cognition, 24, 477–492. Balota, D. A., Pollatsek, A., & Rayner, K. (1985). The interaction of contextual constraints and parafoveal visual information in reading. Cognitive Psychology, 17, 364–388. Binder, K. S., Pollatsek, A., & Rayner, K. (1999). Extraction of information to the left of the fixated word in reading. Journal of Experimental Psychology: Human Perception and Performance, 25, 1162–1172. Brysbaert, M., & Vitu, F. (1998). Word Skipping: Implications for Theories of Eye Movement Control in Reading. In: Eye Guidance in Reading and Scene Perception. (pp. 125–147). G. Underwood, (Ed.). Oxford: Elsevier. Carpenter, P. A., & Just, M. A. (1983). What your eyes do while your mind is reading. In: Eye Movements in Reading: Perceptual and Language processes , (pp. 275–307), K. Rayner (ed.). New York: Academic Press. Djamasbi, S., Siegel, M., Skorinko, J., & Tullis, T. (2011). Online viewing and aesthetic preferences of generation y and the baby boom generation: Testing user web site experience through eye tracking. International Journal of Electronic Commerce, 15(4), 121–158. Dolgunsöz, E. (2015). Measuring Attention in Second Language Reading Using Eye-tracking: The Case of the Noticing Hypothesis. Journal of Eye Movement Research, 8(5). Drieghe, D., Brysbaert, M., Desmet, T., & De Baecke, C. (2004). Word skipping in reading: On the interplay of linguistic and visual factors. European Journal of Cognitive Psychology, 16(1–2), 79–103. Godfroid, A., Boers, F., & Housen, A. (2013). An eye for words: Gauging the role of attention in incidental L2 vocabulary acquisition by means of eye-tracking. Studies in Second language Acquisition, 35(3), 483–517. Henderson, J. M., & Ferreira, F. (1993). Eye movement control during reading: Fixation measures reflect foveal but not parafoveal processing difficulty. Canadian Journal of Experimental Psychology, 47, 201–221. Joe, A. (1995). Text based tasks and incidental vocabulary learning. Foreign language Research, 11(2), 95–111. Just, M. A., & Carpenter, P. (1980). A theory of reading: From eye fixations to comprehension. Psychological Review, 85, 109–130. Liu, P. L. (2014). Using eye tracking to understand the responses of learners to vocabulary learning strategy instruction and use. Computer Assisted Language Learning, 27(4), 330–343. McNeill, A. (1996). Vocabulary Knowledge profiles: Evidence from Chinese speaking ESL speakers. Hong Kong Journal of Applied Linguistics 1(1), 39–63. Pollatsek, A., Reichle, E., & Rayner, K. (2003). Modeling eye movements in reading. In: The Mind’s Eyes: Cognitive and Applied Aspects of Eye Movement Research. (pp. 361–390). J. Hyona, R. Radach, & H. Deubel, (Eds.). Amsterdam: Elsevier. Radach, R., & Kempe, V. (1993). An individual analysis of initial fixation positions in reading. In: Perception and cognition: Advances in eye movement research (pp. 213–226). G. d’Ydewalle & J. Van Rensbergen (Eds.). Amsterdam: North Holland. Rayner, K. (1998). Eye Movements in Reading and Information Processing: 20 Years of Research, Psychological Bulletin, 124 (3), 372–422 Rayner, K., & Fischer, M. H. (1996). Mindless reading revisited: eye movements during reading and scanning are different. Perception & Psychophysics, 58(5), 734–747. Rayner, K., & Well, A. D. (1996). Effects of contextual constraint on eye movements during reading: a further examination. Psychonomic Bulletin & Review, 3, 504–509. Rayner, K., Binder, K. S., Ashby, J., & Pollatsek, A. (2001). Eye movement control in reading: word predictability has little influence on initial landing positions in words. Vision Research, 41(7), 943–954. Rayner, K., Reichle, E. D., & Pollatsek, A. (2005). Eye movement control in reading and the E-Z Reader model. In: Cognitive Processes in Eye Guidance (pp. 131-162). G. Underwood (Ed.),. Oxford: Oxford University Press. Rayner, K., Sereno, S. C., & Raney, G. E. (1996). Eye movement control in reading: a comparison of two types of models. Journal of Experimental Psychology: Human Perception and Performance, 22, 1188–1200. Reichle, E., Pollatsek, A., Fisher, D. L., & Rayner, K. (1998). Toward a model of eye movement control in reading. Psychological Review, 105, 125–157. Scarcella, R. & C. Zimmerman (1998). ESL student performance on a text of academic lexicon. Studies in Second language Acquisition, 20(1), 27–49. Schilling, H. E., Rayner, K., & Chumbley, J. I. (1998). Comparing naming, lexical decision, and eye fixation times: Word frequency effects and individual differences. Memory & Cognition, 26(6), 1270–1281. Schroeder, S., Hyönä, J., & Liversedge, S. P. (2015). Developmental eye-tracking research in reading: Introduction to the special issue. Journal of Cognitive Psychology, 27(5), 500–510. Smith, B. (2012). Eye tracking as a measure of noticing: A study of explicit recasts in SCMC. Language Learning & Technology, 16(3), 53–81. Wesche, M. & T. Paribakht (1996). Assessing vocabulary knowledge: depth vs. breadth. Canadian Modern Language Review, 53(1), 13–40. Winke, P., Gass, S., & Sydorenko, T. (2013). Factors Influencing the Use of Captions by Foreign Language Learners: An Eye‐Tracking Study. The Modern Language Journal, 97(1), 254–275.